A case–control study of sporadic retinoblastoma in relation to maternal health conditions and reproductive factors: a report from the Children's Oncology group. Issue 1 (December 2015) - Heck, Julia; Omidakhsh, Negar; Azary, Saeedeh; Ritz, Beate; von Ehrenstein, Ondine; Bunin, Greta; Ganguly, Arupa
Abstract Background The early age at retinoblastoma occurrence, the most common eye malignancy in childhood, suggests that perinatal factors may contribute to its etiology. Methods In a large multicenter study of non-familial retinoblastoma, we conducted structured interviews with the parents of 280 cases and 146 controls to elicit information on health during the perinatal period. We used unconditional logistic regression to assess associations between retinoblastoma and parental fertility treatment, birth control use in the year prior to pregnancy, maternal health conditions and the use of prescription medications during pregnancy, and whether mothers breastfed the index child. Results Bilateral retinoblastoma was related to maternal underweight (body mass index <18.5) prior to pregnancy [Odds Ratio (OR) = 4.5, 95 % confidence interval (CI) 1.0, 20]. With regards to unilateral retinoblastoma, we observed a negative association with the use of condoms in the year prior to pregnancy (OR = 0.4, CI 0.2, 0.9), and a trend towards a positive association with maternal diabetes (OR = 2.2, CI 0.8, 6.6). Conclusions Results from our study suggest a role for several maternal health and reproductive factors. Given that there are few epidemiologic studies of retinoblastoma, our results require replication in studies which utilize medical record review.